Pythagorean Nanogeneralized Closed Sets with Application in Decision-Making. (26th December 2021) - Ajay, D.; Charisma, J. Joseline; Petaratip, T.; Hammachukiattikul, P.; Boonsatit, N.; Younis, Jihad A.; Rajchakit, G.
Abstract : Topology is studying the objects which are considered to be equal if they may also be continually deformed through other shapes as bending and twisting without tearing or glueing them. Topology is similar in geometrical structures and quantitatively equivalent. Nanotopology is the study of set. The main goal of this article is to propose the idea of generalized closed sets in Pythagorean nanotopological spaces. In addition, the concept of semigeneralized closed sets is also defined, and their properties are investigated. An application to MADM using Pythagorean nanotopology has been proposed and illustrated using a numerical example.